Processo eletrônico : um estudo de caso etnográfco do registro audiovisual da tomada de depoimento pessoal - Lopes, Francisco Cristiano (2012)
This paper deals with the event taking testimony from the audiovisual methodology Ethnographic Case Study. This study is justified by procedural changes arising from art. 187 of the Code of Criminal Procedure, with the wording included by Law No. 10,792 of 1 December 2003, which prescribes the manner in which the judge must conduct the examination of the defendant. The motivation for this work came from the need to employ new perspectives in legal research determined by the principle of transdisciplinarity. Hence the use of theoretical and methodological assumptions of linguistics and ethnography, which will enable such transgress legal boundaries in order to devise possible solutions to complex problems and present, such as those related to Information Society and application of Information and Communication Technologies in proceedings. The objective of this work is the description of the event taking of testimony in the electronic process of Brazilian justice, comparing where possible to take the deposition event traditionally, using ethnographic description of the taking of testimony from the methodology developed by Virginia Necklaces, as parameter to our research. The methodology used, it is an Ethnographic Case Studyexplanatory descriptive observational research developed through the event making audiovisual testimony. The survey was conducted in two stages: first, observational, which includes the notes of testimony taken audiovisual event, the second descriptive, explanatory, which includes the analysis of the main features of the electronic process, but notably, the testimony of the audiovisual which may involve the use of standardized techniques for data collection. Search to find out that the traditional system of registration statements, by reducing the term made by the judge, after hearing the witness, is flawed because it does not allow the complexity of the testimony be effectively reflected in the paper, not capturing the expressions, doubts, certainties and other relevant aspects of the testimony. The audiovisual record of the testimony allows the overcoming of certain incompleteness of the taking of testimony with reduced term because it will reflect all with unmatched reliability of the testimony, not just the impression that the judge had his instructor and, personally, sent to paper